(untitled) (World Economics and Finance Bulletin, 2025)
It is mostly the custom when evaluating the performance of the administrative units and its employees by the traditional methods, so an incomplete and unrealistic image is shown , this necessitate the adoption of some modern methods of evaluation, that include the balance scorecard ( BSC ). The study aims to explain the balanced performance card , and then to assess the efficiency of the of accountants and auditors’ professional performance in the administrative units operating in Wasit Governorate. To achieve the mentioned goal, a questionnaire has been adopted and distributed to the members of the stud sample, that consists of the administrative units working under Wasit Governorate leadership . The sample consists of 71 accountants and auditors employed the mentioned administrative units . Using the SPSS package to analyze and test the hypothesis , the study found a high correlation between the two variables . So, in the light of the drawn conclusions , a set of recommendations was set . The most important one is the need to apply the BSC in evaluating the performance of accountants and auditors at Wasit Governorate’ administrative units, and to develop a BSC culture within the organizational culture of the mentioned governorate.